2002
DOI: 10.1159/000057745
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Nasal Mucosal G Protein Levels and Histamine Receptor Affinity in a Guinea Pig Model of Nasal Hyperresponsiveness

Abstract: Background: Nasal hyperresponsiveness is a common feature of allergic rhinitis, but the underlying mechanisms have yet to be elucidated. The effects of repeated antigen inhalation on the characteristics of histamine H1 receptors and expression levels of heterotrimeric guanosine 5′-triphosphate-binding proteins in nasal mucosa were investigated to understand the mechanisms of the pathogenesis of nasal hyperresponsiveness in allergic rhinitis. Methods: Male Hartley guinea pigs were sensitized by the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…This study clearly showed an increased expression of iNOS in nasal mucosa of a guinea pig allergic rhinitis model. 12 On the other hand, no change in the expression levels of eNOS and nNOS in nasal mucosa was observed in this animal model of allergic rhinitis. The results might be consistent with previous reports in upper and lower airways in allergy, 13,19,20 suggesting that iNOS may play an important role in the pathogenesis of allergic airway diseases, such as asthma and rhinitis.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This study clearly showed an increased expression of iNOS in nasal mucosa of a guinea pig allergic rhinitis model. 12 On the other hand, no change in the expression levels of eNOS and nNOS in nasal mucosa was observed in this animal model of allergic rhinitis. The results might be consistent with previous reports in upper and lower airways in allergy, 13,19,20 suggesting that iNOS may play an important role in the pathogenesis of allergic airway diseases, such as asthma and rhinitis.…”
Section: Discussionmentioning
confidence: 65%
“…An allergic rhinitis model was prepared as previously reported. 12 In brief, guinea pigs were sensitized by inhalation of dinitrophenylated ovalbumin antigen (DNP-OVA; 10 mg of protein/mL) with an ultrasonic nebulizer (TUR-3000; Nihon Kohden, Tokyo, Japan) for 10 minutes under the unanesthetized condition in a Plexiglas box (300 ϫ 200 mm, 150-mm height; day 0). Seven days after the sensitization (day 7), the animals were boosted by the same inhalation procedure described previously.…”
Section: Sensitization and Antigen Challengementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the nasal hyperresponsiveness in chronic allergic rhinitis might be explained in part by an elevation of G-protein levels that might increase the binding affinity of histamine to its receptors, increase recycling of functional H1-R to the cell surface after activation, or promote H1-R-G-protein coupling. These mechanisms could augment histamine-induced nasal responses [14].…”
Section: H1 Receptorsmentioning
confidence: 99%